XL888 and pembrolizumab modulate the immune landscape of colorectal tumors in a phase Ib/II clinical trial - Maggie J. Phillips; Olatunji B. Alese; Natalie K. Horvat; Emily Greene; Olumide B. Gbolahan; Kathleen Coleman; Deon B. Doxie; Vaunita Parihar; Zaid K. Mahdi; Ashley McCook-Veal; Jeffrey M. Switchenko; Maria Diab; et al. (OncoImmunology)
We conducted a phase Ib/II clinical trial to evaluate the safety, feasibility, and clinical activity of combining pembrolizumab (anti-PD-1) with XL888 (Hsp90 inhibitor) in patients with advanced colorectal cancer (CRC). We hypothesized that this regimen would modulate soluble and cellular immune mediators and enhance clinical outcomes. The trial employed a 3 + 3 open-label design, with an expansion cohort at the recommended phase II dose (RP2D) in treatment-refractory, mismatch repair-proficient CRC patients. Comprehensive analyses of plasma cytokines, peripheral blood mononuclear cells (PBMCs), and spatial immune cell patterns in liver biopsies were performed to identify unique immune signatures resulting from the combined therapy. The combination of pembrolizumab and XL888 proved to be safe and feasible, with a subset of patients achieving stable disease, although no objective responses were observed in this heavily pre-treated population. Correlative studies revealed immunomodulatory effects in tumors and circulation, including a reduction in IL6+ cells and macrophages (CD68+) within metastatic liver tissue, alterations in blood CD3+ cells, and upregulation of numerous inflammatory plasma cytokines. These findings suggest local and systemic immune activation by the combination of pembrolizumab and XL888. While clinical activity was modest in treatment-refractory CRC patients, there were notable effects on the tumor immune environment and systemic immune modulation.